Specification for interconnection of electrical apparatus, constructed to two or more British Standards, for use in mines susceptible to firedamp (BSI, 1986)
Electrical equipment, Mining equipment, Mineral extraction equipment, Fire-damp, Protected electrical equipment, Interfaces, Type d protected electrical equipment, Type e protected electrical equipment, Type i protected electrical equipment, Electric enclosures, Marking, Marks, Labels, Graphic characters, Size